Donald Locke - resistant forms / editors, Gina Buenfeld-Murley [and five others]. - Buenfeld-Murley, Gina; Locke, Donald (Spike Island, 2025)
A fully illustrated monograph celebrating the first major survey exhibition of Donald Locke (1930-2010), organised by Spike Island, Bristol, Ikon Gallery, Birmingham, and Camden Art Centre, London.